Application of Trichoderma Hz36 and Hk37 as Biocontrol Agents against Clubroot Caused by Plasmodiophora brassicae - Yanli Zhao; Xingfu Chen; Jiasen Cheng; Jiatao Xie; Yang Lin; Daohong Jiang; Yanping Fu; Tao Chen (Journal of Fungi, 2022)
Clubroot, a soil-infective disease caused by Plasmodiophora brassicae, is a serious disease affecting cruciferous plants around the world. There is no effective control measure to completely remove this pathogen from fields after infection. Here, we screened and identified two strains (Hz36, Trichoderma guizhouense; Hk37, Trichoderma koningiopsis) of Trichoderma from the gall of clubroot in rapeseed fields with biocontrol potential for clubroot. The fermentation broth of Hz36 could significantly inhibit the germination of resting spores of P. brassicae, and promote the seed germination and root growth of rapeseed. The biocontrol efficiency of Hz36 strain on clubroot for rapeseed and Arabidopsis thaliana was 44.29% and 52.18%, respectively. The qPCR results revealed that strain Hz36 treatment could significantly reduce the content of P. brassicae in root cells, and paraffin section analysis revealed that it could delay the development of P. brassicae. Strain Hk37 showed similar effects to strain Hz36, whose biocontrol efficiency of clubroot could reach 57.30% in rapeseed and 68.01% in A. thaliana. These results indicate that strains Hz36 and Hk37 have the potential for the biocontrol of clubroot.